Pengenalan Enterpreunership Multimedia Pada Santri Pondok Pesantren At-Taubah Tirta Mulya - Agustia Hananto; Elfina Novalia; Tukino Tukino (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
This community service activity aims to introduce the concept of multimedia entrepreneurship to students of the At-Taubah Tirta Mulya Islamic Boarding School, Karawang, in order to improve their knowledge and skills in utilizing multimedia as a tool for entrepreneurship. Held on March 2, 2024, this activity involved 50 students who attended lecture sessions, discussions, and multimedia content creation practices. The research method used was participatory action research, which allowed participants to be actively involved in the learning process. Data were collected through observation, interviews, and questionnaires to measure changes in knowledge before and after the activity. The results of the analysis showed a significant increase in students' understanding and skills related to multimedia entrepreneurship. The implications of this activity highlight the importance of collaboration between higher education institutions and Islamic boarding schools to create a creative and independent generation in the digital era.